2023
DOI: 10.3390/membranes13060548
|View full text |Cite
|
Sign up to set email alerts
|

New Network Polymer Electrolytes Based on Ionic Liquid and SiO2 Nanoparticles for Energy Storage Systems

Abstract: Elementary processes of electro mass transfer in the nanocomposite polymer electrolyte system by pulse field gradient, spin echo NMR spectroscopy and the high-resolution NMR method together with electrochemical impedance spectroscopy are examined. The new nanocomposite polymer gel electrolytes consisted of polyethylene glycol diacrylate (PEGDA), salt LiBF4 and 1—ethyl—3—methylimidazolium tetrafluoroborate (EMIBF4) and SiO2 nanoparticles. Kinetics of the PEGDA matrix formation was studied by isothermal calorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Earlier in Reference [ 36 ], for a similar electrolyte system but with the introduction of SiO 2 nanoparticles, only one mobility coefficient was observed for all of the components of the system. In addition, it was shown that the electrolyte based on SiO 2 , with the same composition of all other components (ionic liquid, salt, polymer, and EC), had conductivity with respect to lithium ions sufficient for its use in lithium–organic batteries.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Earlier in Reference [ 36 ], for a similar electrolyte system but with the introduction of SiO 2 nanoparticles, only one mobility coefficient was observed for all of the components of the system. In addition, it was shown that the electrolyte based on SiO 2 , with the same composition of all other components (ionic liquid, salt, polymer, and EC), had conductivity with respect to lithium ions sufficient for its use in lithium–organic batteries.…”
Section: Resultsmentioning
confidence: 86%
“…In a previous work [ 36 ], a SiO 2 nanoparticle was modeled by a Si 17 O 28 (OH) 12 cluster. When studying its interaction with electrolyte components, it was found that the formation of the adsorption complex {Si 17 O 28 (OH) 12 (Li BF 4 ) 2 (EMI BF 4 ) 2 } reduces the energy of the system by 1.47 eV.…”
Section: Resultsmentioning
confidence: 99%